Time-dependent effects of cellulose and gelatin-based hemostats on cellular processes of wound healing - Wagenhäuser, Markus U.; Garabet, Waseem; van Bonn, Mia; Ibing, Wiebke; Mulorz, Joscha; Hyun Rhee, Yae; Spin, Joshua; Dimopoulos, Christos; Oberhuber, Alexander; Schelzig, Hubert; Simon, Florian (Archives of medical science, 2023)
Oxidized regenerated cellulose-based (ORC - TABOTAMP), oxidized non-regenerated cellulose-based (ONRC - RESORBA CELL), and gelatin-based (GELA - GELITA TUFT-IT) hemostats are commonly used in surgery. However, their impact on the wound healing process remains largely unexplored. We here assess time-dependent effects of exposure to these hemostats on fibroblast-related wound healing processes. Hemostats were applied to fibroblast cell cultures for 5-10 (short-), 30 and 60 min (intermediate-) and 24 h (long-term). Representative images of the hemostat degradation process were obtained, and the pH value was measured. Cell viability, apoptosis and migration were analyzed after the above exposure times at 3, 6 and 24 h follow-up. Protein levels for tumor necrosis factor α (TNF-α) and transforming-growth factor β (TGF-β) were assessed. ORC and ONRC reduced pH values during degradation, while GELA proved to be pH-neutral. Hemostat structural integrity was prolonged for GELA (vs. ORC and ONRC). TGF-β and TNF-α levels were reduced for ORC and ONRC (vs. GELA and control) ( < 0.05). Further, exposure of ORC and ONRC for longer than 5-10 min reduced cell viability vs. GELA and control at 3 h post-exposure ( < 0.05). Similarly, cell migration was impaired with ORC and ONRC exposure longer than 60 min at 24 h follow-up ( < 0.05). Short-term exposure to ORC and ONRC impairs relevant wound healing-related processes in fibroblasts, and alters protein levels of key mediating cytokines. GELA does not show similar effects. We conclude that GELA may be preferred over ORC and ONRC over short-, intermediate- and long-term exposures. Future validation of the clinical relevance is warranted.